Role of MicroRNAs in the Pathogenesis of Coronary Artery Disease - Ghafouri-Fard, Soudeh; Gholipour, Mahdi; Taheri, Mohammad (Frontiers in Cardiovascular Medicine, 2021)
Coronary artery disease (CAD) is the main reason of cardiovascular mortalities worldwide. This condition is resulted from atherosclerotic occlusion of coronary arteries. MicroRNAs (miRNAs) are implicated in the regulation of proliferation and apoptosis of endothelial cells, induction of immune responses and different stages of plaque formation. Up-regulation of miR-92a-3p, miR-206, miR-216a, miR-574-5p, miR-23a, miR-499, miR-451, miR-21, miR-146a, and a number of other miRNAs has been reported in CAD patients. In contrast, miR-20, miR-107, miR-330, miR-383-3p, miR-939, miR-4306, miR-181a-5p, miR-218, miR-376a-3p, and miR-3614 are among down-regulated miRNAs in CAD. Differential expression of miRNAs in CAD patients has been exploited to design diagnostic or prognostic panels for evaluation of CAD patients. We appraise the recent knowledge about the role of miRNAs in the development of diverse clinical subtypes of CAD.